2009
DOI: 10.1017/s0029665109991868
|View full text |Cite
|
Sign up to set email alerts
|

Plenary Lecture 3 Food and the planet: nutritional dilemmas of greenhouse gas emission reductions through reduced intakes of meat and dairy foods

Abstract: Legally-binding legislation is now in place to ensure major reductions in greenhouse gas emissions in the UK. Reductions in intakes of meat and dairy products, which account for approximately 40% of food-related emissions, are an inevitable policy option. The present paper assesses, as far as is possible, the risk to nutritional status of such a policy in the context of the part played by these foods in overall health and well-being and their contribution to nutritional status for the major nutrients that they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(85 citation statements)
references
References 88 publications
(135 reference statements)
3
71
0
7
Order By: Relevance
“…The WHO also recommends reductions in the consumption of trans fats, which were not included in the current analysis as trans fat reductions are generally achieved at the industrial stage rather than by changes in diet. Although many micronutrients are considered important for health, previous research has shown that meat production is responsible for a large proportion of dietary carbon emissions (15) ; therefore we extracted data on micronutrients that have been highlighted as potentially deficient in a low-meat diet (16) . We used a modified QUADAS-2 tool (17) to assess the risk of bias in individual studies.…”
Section: Methodsmentioning
confidence: 99%
“…The WHO also recommends reductions in the consumption of trans fats, which were not included in the current analysis as trans fat reductions are generally achieved at the industrial stage rather than by changes in diet. Although many micronutrients are considered important for health, previous research has shown that meat production is responsible for a large proportion of dietary carbon emissions (15) ; therefore we extracted data on micronutrients that have been highlighted as potentially deficient in a low-meat diet (16) . We used a modified QUADAS-2 tool (17) to assess the risk of bias in individual studies.…”
Section: Methodsmentioning
confidence: 99%
“…These movements are often supported by scientific literature examining the environmental impact of reduced meat consumption (Pimentel & Pimentel, 2003;Millward & Garnett, 2010). For example, Weber & Matthews (2008) conclude that "Switching less than one day per week's worth of calories from red meat and dairy products to chicken, fish, eggs or a vegetable-based diet achieves more greenhouse gas reductions than buying all locally-sourced food".…”
Section: Limitations Of the Global Vegetarian/vegan Ideologymentioning
confidence: 99%
“…It is entirely possible to achieve a balanced vegetarian diet (although more difficult for vegans, especially growing children or pregnant women) and denizens of developed regions could arguably reduce their animal-source food consumption without conferring major negative health effects. Yet the impact of removing sources of highly-digestible essential macro-and micro-nutrients from the diets of inhabitants of developing regions could have a significant detrimental effect on human wellbeing (Millward & Garnett, 2010;Smith et al, 2012). Within developing regions, the average person consumes approximately 25% of the daily allowance of dairy products recommended for optimum health (Blaskó, 2011) and nutritional deficiencies associated with a lack of animal-source foods include low birthweights, impaired cognitive and motor development, rickets and anaemia (Neumann et al, 2002;Traoré et al, 2012).…”
Section: Limitations Of the Global Vegetarian/vegan Ideologymentioning
confidence: 99%
“…It has been found that meat-centric meals generate on average nine times higher greenhouse gas emissions than plant-based equivalents [5], while specific meat-based products such as beef and cheese cause 10-20 times more environmental impact [87][88][89]. An animal-based diet requires 2.5-5.0 times the energy inputs [7,[90][91][92][93], 2-3 times the water, 13 times the fertilizer, and 1.4 times the pesticide use per calorie produced compared with a plant-based diet [7,93,94].…”
Section: Reducing Meat and Animal-based Foodsmentioning
confidence: 99%
“…However, it should be noted that from a food security and diet perspective, vegan and vegetarian diets, though lower in environmental impacts, have nutritional risks [133]. Specifically, there is greater potential for the insufficient intake of certain micronutrients [41,88,134]. This matters most when diet is of a monotonous limited selection, when even a small animal-based food intake could make a critical difference to micronutrient intake [75][76][77].…”
Section: Increasing Fruit and Vegetable Intakementioning
confidence: 99%